MEKANISME PENGGUNAAN JAMINAN KEBENDAAN (RAHN TASJILY) DALAM PEMBIAYAN BANK SYARIAH DI INDONESIA DAN MALAYSIA - Hidayati, Tri; Syarifuddin, Syarifuddin; Pelu, Ibnu Elmi AS.; Syaikhu, Syaikhu; Hussain, Mohammad Azam; Nor, Mohd Zakhiri Md.; Azhar, Alias (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The main objective of this legal research is to compare the legal construction and the use of “rahn tasjily” mechanism in the Sharia bank financing between Indonesia and Malaysia through law, concept, and history approaches. The data were analyzed qualitatively by systematic interpretation and historical interpretation. The results are: 1) Both countries do not have a strong regulation in Sharia guarantees, thus the law construction is implemented by harmonization and integration between Sharia principles and conventional regulations (civil). The differences are in the concept, the division of rahn, and the law substance in the Sharia banking complement regulation. 2) The mechanism is also different, where in Indonesia the guarantee should be bound by an authentic certificate (notary) and registered in the authority institutions in order that Sharia bank (murtahin) obtains a strong law protection beside an insurance. While in Malaysia, the use of collateral is only included in the financing contract without an authentic certificate; the registration is not compulsory and the ownership proof of guarantee (marhun bih) as well as the object is in rahin permanently (except a land); and the collateral strength for Sharia bank is an insurance.